2015
DOI: 10.7575/aiac.ijalel.v.4n.6p.190
|View full text |Cite
|
Sign up to set email alerts
|

Communication Apprehension: A Comparison between English Majors and Non-majors in China

Abstract: Using the scale of communication apprehension developed by McCroskey, a comparative study has been conducted between English majors and non-majors of different English learning experiences in a Chinese university. Whereas all the subjects remain at the medium level of communication apprehension, no significant difference was found across different communication scenarios among students of different majors as well as different grades. The results imply that the cause of communication apprehension might not be n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
3
4
0
Order By: Relevance
“…There are differences between these groups for the different oral communication apprehension levels. When analyzing the full sample, we found that speaking at meetings was where students are less comfortable, with women achieving a higher score than men, corroborating previous studies [33][34][35]. However, most of the literature reviews [3,[11][12][13] had the same results as this article.…”
Section: Oral Communication Apprehensionsupporting
confidence: 88%
See 3 more Smart Citations
“…There are differences between these groups for the different oral communication apprehension levels. When analyzing the full sample, we found that speaking at meetings was where students are less comfortable, with women achieving a higher score than men, corroborating previous studies [33][34][35]. However, most of the literature reviews [3,[11][12][13] had the same results as this article.…”
Section: Oral Communication Apprehensionsupporting
confidence: 88%
“…In the full sample, the total OCA values were within the average, with typical results (50-80) [42]. Considering these results, we could identify the main difficulties as being oral communication apprehension for the women group [35].…”
Section: Oral Communication Apprehensionsupporting
confidence: 53%
See 2 more Smart Citations
“…Existing published evidence has demonstrated that there are slight gender differences in total PRCA-24 scores. [32][33][34] These differences are often ascribed to the cultural biases resulting from social roles and psychological stereotypes of the genders. 35,36 Some researchers argue that in a patriarchal society, women are silenced and so they develop fear and anxiety toward expressing themselves.…”
Section: Discussionmentioning
confidence: 99%